A review of herb-induced liver injury in mainland china - Yang, Yan; Ge, Fei-Lin; Tang, Jin-Fa; Qin, Shuang-Lin; Zeng, Rui; Yao, Meng-Lin; Xiao, Xiao-He; Bai, Zhao-Fang; Tang, Cheng-Lin (Frontiers in Pharmacology, 2022)
Traditional medicines have greatly contributed to people’s health worldwide. However, in recent years, the frequent occurrence of herb-induced liver injury (HILI) has raised public concerns regarding the safety of herbs. HILI not only severely impacts public health, thus increasing its medical burden, but also consumes medical resources. However, the pharmacoepidemiology and risk factors of HILI are still unclear due to the complexity of herbs (medication theory, drug composition, dual properties of drugs and food, etc.). China is the country with the most extensive use of herbs and cases of HILI worldwide. The safety profile of herbs (especially with respect to HILI) has also affected the use of herbs internationally. Therefore, this review focuses on the epidemic situation of HILI in mainland China to compile its characteristics, while focusing on the three main aspects of patients, drugs, and unreasonable prescriptions to explore the potential risk factors. Our objective was to provide a reference for HILI pharmacovigilance and risk prevention and control and contribute to Chinese knowledge of the realisation of the “Medication without Harm” global safe medication strategic goal of the World Health Organization.